Influence of Seasons and Tides on the Distribution of Enteric Protozoa on the Shores of the Atlantic Ocean in Kribi (South Region of Cameroon): Health Risks Related to Bathing - Paul Alain Nana; Majesté Pahane Mbiada; Siméon Tchakonté; Karine Moche; Rodrigue Steve Mouchili Palena; Moïse Nola; Télesphore Sime-Ngando (Pollutants, 2023)
Beaches are major sites of microbiological pollution. Assessment of the abundance of resistant forms of enteric protozoa on these recreational waters is important for the prevention and management of health risks. Based on sedimentation and flotation methods, this study found that Kribi beach waters concentrate considerable amounts of enteric protozoa, which are potentially pathogenic. They include Coccidia (Cryptosporidium sp. and Cyclospora cayetanensis), Amoebae (Endolimax nana, Entamoeba histolytica and Entamoeba coli) and Flagellates (Giardia intestinalis). In general, seasonal changes and tidal cycles have significantly impacted the spread of these parasites along Kribi beaches. Thus, at all sites surveyed (Mpalla, Ngoyè and Mboamanga), maximum protozoan abundances were recorded at low tide and during the rainy seasons. It should also be noted that at each sampling site, significant correlations were recorded between certain protozoa and certain physico-chemical variables (p < 0.05). At Mboamanga, for example, Cryptosporidium sp. and Endolimax nana were positively correlated during the Short Rainy Season with temperature (r = 0.601, p = 0.044 and r = 0.632, p = 0.042). At Mpalla, a positive and significant correlation was observed during the Short Rainy Season between Entamoeba coli and pH (r = 0.605, p = 0.033). The high concentration of resistant forms of these enteric protozoa at Kribi beaches is a real public health threat for bathers. Therefore, in this tourist town, it is urgent to put in place an effective plan for the collection and sustainable treatment of solid and liquid waste, which are the main sources of contamination.